Breast cancer risk in women who fulfill high-risk criteria: at what age should surveillance start? - Brandt, Andreas; Lorenzo Bermejo, Justo; Sundquist, Jan; Hemminki, Kari (Breast cancer research and treatment, 2010)
Family history is a strong predictor of hereditary breast cancer, particularly when it includes cases of early onset or bilateral breast cancers and multiple cases of breast or ovarian cancers. This article provides relative risks and cumulative risks of breast cancer in women whose family history indicates high risk. Specifically, the aim was to determine how many years earlier the high-risk women reach the cumulative risk of women without family history at the age at which screening in average-risk women is initiated. The women of the nation-wide Swedish Family-Cancer Database were classified according to clinical criteria based on family history suggesting high risk for hereditary breast ovarian cancer syndrome. The relative risks of breast cancer were calculated as hazard ratio using Cox regression. Cumulative risks of breast cancer were estimated with a stratified Cox model based on Tsiatis’ method. The hazard ratios of breast cancer for the considered criteria ranged from 1.50 to 5.99. The cumulative risks ranged from 1 to 10% by age 50 years. The age to reach the same cumulative risk as women lacking a family history at the age of 50 years ranged between 32.0 and 40.8 years. Relative and cumulative risks of women at high risk of breast cancer associated with different clinical criteria were diverse, which may be helpful in considering when current clinical criteria are revised. According to the present results, current recommendations of starting clinical interventions 10 years earlier in high-risk women, based on expert opinions, appear justified at least for the largest high-risk groups.
Erstmals am 30. Juli 2009 online veröffentlicht
Gesehen am 08.02.2023